Mpath maps multi-branching single-cell trajectories revealing progenitor cell progression during development - Jinmiao Chen (Nature Portfolio, 2016)
The tools for constructing cell lineages from single cell data are limited. Here, the authors present Mpath: an algorithm to derive multi-branching trajectories using neighbourhood-based cell state transitions, and use this to predict developmental trajectories in dendritic and muscle cells.